2002
DOI: 10.1680/muen.2002.151.1.39
|View full text |Cite
|
Sign up to set email alerts
|

TravelSmart—large-scale cost-effective mobility management. Experiences from Perth, Western Australia

Abstract: Travel demand management or mobility management is growing in interest as political decision-makers realise that it is not financially and socially feasible to attempt to build enough roads to satisfy growing car use. In reaching this conclusion, political decision-makers confront a dilemma. Car users want quicker travel times for their car trips but they are not prepared to suffer the negative impacts of excessive car use. The solution lies in changing the travel behaviour of individuals but not through measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…In the Australian states of Victoria and Western Australia, their “TravelSmart” social marketing campaigns to reduce car journeys used survey data to identify households potentially interested in cycling as a transport alternative and then provided them with cycling route maps and other information to make cycling travel solutions more accessible and practicable. In the case of the pilot city of Perth, this led to a 90 per cent increase in cycling levels during the first year (James, 2002). Such campaigns have encouraged a move away from car commuting and towards cycling in Australia that saw bike purchases outstrip new car sales during 2006. Social costs of involvement instead of “Price” .…”
Section: Climate Change Communication – Insights From Social Marketingmentioning
confidence: 99%
“…In the Australian states of Victoria and Western Australia, their “TravelSmart” social marketing campaigns to reduce car journeys used survey data to identify households potentially interested in cycling as a transport alternative and then provided them with cycling route maps and other information to make cycling travel solutions more accessible and practicable. In the case of the pilot city of Perth, this led to a 90 per cent increase in cycling levels during the first year (James, 2002). Such campaigns have encouraged a move away from car commuting and towards cycling in Australia that saw bike purchases outstrip new car sales during 2006. Social costs of involvement instead of “Price” .…”
Section: Climate Change Communication – Insights From Social Marketingmentioning
confidence: 99%
“…Sin embargo, dado que la mercadotecnia social está más enfocada en servicios que en productos físicos, no es apropiado referirse a la distribución o temas de lugar sino a accesibilidad (Peattie y Peattie, 2009). Un caso ilustrativo es la campaña llevada a cabo en Australia para promover el transporte en bicicleta como medio alternativo; ésta logró un incremento del 90% en tal actividad, en el primer año del piloto realizado en la ciudad de Perth, al proveer rutas de ciclismo y otra información para dar mayor accesibilidad y viabilidad a tal acción (James, 2002).…”
Section: Plaza (Distribución) / Accesibilidadunclassified
“…El marketing social comparte el interés de la mercadotecnia comercial pero en una comunicación de dos vías, que implica interacción y construcción de relaciones para motivar la aceptación, adopción y mantenimiento de una propuesta o conducta social particular (Peattie y Peattie, 2009). En la campaña de uso de bicicleta en Arhus, Dinamarca, además del uso de medios convencionales de comunicación de mercadotecnia como folletos y eventos, se empleó adicionalmente un medio más interactivo como el firmar contratos con los participantes para comprometerlos en reducir el uso del automóvil (James, 2002).…”
Section: Promoción / Comunicación Socialunclassified
“…Australia has experienced a number of policies aimed at influencing travel behaviours. James (2002) discusses the success of a low‐cost, voluntary behaviour change programme, TravelSmart, implemented in Perth. It was observed that the TravelSmart programme was able to achieve a modal shift and provide a very cost‐effective alternative to building expensive road infrastructure solutions (Goulias et al ., 2002).…”
Section: Measures To Promote Sustainable Transport Choicementioning
confidence: 99%